The effect of predictor variables on employee engagement and organizational commitment and employee performance - Hengki Degrafe Linggiallo; Sukisno S. Riadi; Sugeng Hariyadi; Doddy Adhimursandi (Management Science Letters, 2020)
The purpose of this study was to examine and analyze the influence of personality, motivation, job satisfaction, employee engagement, organizational commitment on employee performance in PT. PLN (Persero) The Power Generation Unit of Mahakam, Indonesia. There were 167 employees par-ticipated in this survey using a saturated sample in which all populations were sampled. The research model used in this study was a structural model to test the hypotheses proposed by the SEM (Structure Equation Modeling) analysis technique using the Warp PLS 6.0 program approach. The results show that personality and job satisfaction had a positive and significant effect on employee engagement. Motivation was not significant to employee engagement. Personality and motivation were not significant to organizational commitment. Job satisfaction had positive and significant effect on organizational commitment. Personality, motivation, and job satisfaction did not have significant effect on employee performance. Employee engagement was positive and significant for organizational commitment. Employee engagement and organizational commitment were positive and significant for employee performance.